Epidemiological and clinical characteristics of the first 557 successive patients with COVID-19 in Pernambuco state, Northeast Brazil. Issue 38 (November 2020) - Magalhães, Jurandy Júnior Ferraz de; Mendes, Renata Pessoa Germano; Silva, Caroline Targino Alves da; Silva, Severino Jefferson Ribeiro da; Guarines, Klarissa Miranda; Pena, Lindomar; ,
Abstract: Background: South America is the current epicenter of COVID-19 pandemic. Yet, the epidemiological and clinical features of the disease have not been described in Brazil, the third most affected country in the world. Methods: In this retrospective study, we describe the demographics, epidemiology and clinical features of the first 557 consecutive patients positive for SARS-CoV-2 living in Pernambuco state, Northeast Brazil. Results: The first COVID-19 cases occurred in the high income population. The age of infected patients ranged from 27 days to 97 years with a median of 47 years. The ratio of males to female in the SARS-CoV-2-infected group was 0.83:1. The most common symptom was cough (74.51%), followed by fever (66.79%), dyspnea (56.01%), sore throat (28.19%) and O2 saturation <95% (24.42%). 86.44% of the lethal cases were patients older than 51 years. The median time from illness onset to diagnosis was 4.0 days (range 0–39 days) Severe patients diagnosed after 14 days of symptoms onset had higher viral load than patients with mild disease. Conclusions: Our study provides important information about COVID-19 in the tropics and will assist physicians and health officials to face the current pandemics as SARS-CoV-2 continues to spread in the human population. Highlights: We describe for the first time the demographics, epidemiology and clinical of COVID-19 in Brazil. . The first COVID-19 cases occurred in the high income population. 86.44% of the lethal cases were patients older than 51 years. Severe patients diagnosed after 14 days of symptoms onset had higher viral load than patients with mild disease.